The Role of Social Media in Shaping Gen Z`s Perception About The World of Work and its Influence on IT Job Search Process - Novitasari, Devi; Mauludin, Hanif (AGUSPATI Research Institute, 2025)
This study aims to analyze the role of social media in influencing Generation Z's job search process, both directly and through perceptions of the world of work. Social media now functions not only as a means of entertainment and communication, but also as a primary source of career information for Generation Z. This study uses a quantitative approach with a survey method of Generation Z respondents. The data analysis technique used is linear regression with a mediation test. The results of the study indicate that the role of social media has a significant influence on the job search process. In addition, social media also has a significant influence on Generation Z's perceptions of the world of work. Furthermore, Generation Z's perceptions are proven to act as a mediating variable in the relationship between social media and the job search process. These findings confirm that social media plays a strategic role in shaping Generation Z's perceptions and behavior in job searching. The implication of this study is the need for more optimal use of social media, both by job seekers and by companies, especially in employer branding strategies to attract the attention of Generation Z.